PRIVATIZATION OF PUBLIC ENTERPRISES IN NIGERIA: IMPACT ON EMPLOYEES’ PERFORMANCE AND MANAGERIAL IMPLICATIONS - Osunde, Carl (International Journal of Research -GRANTHAALAYAH, 2015)
Privatization is the transfer of assets, ownership and control of state owned enterprises from the public sector to private sector. This research was conducted to examine the impact of privatization on employees’ performance and managerial implications as a result of privatization of public enterprises. This current study reveals that post privatization can lead to massive job cuts, job insecurity especially among junior workers. Privatization increase job satisfaction, training and development opportunities, increase in salary and favourable working conditions which improves employees’ productivity and performance. This present research was conducted using respondents from Dangote Cement PLC, a privatized company previously known as Benue Cement Company in Nigeria and the findings of this research matched with previous researches on the impact of privatization in developed and developing countries such as United Kingdom, Japan, Nigeria, India and Ghana.